THE PREVALENCE AND CLINICAL SIGNIFICANCE OF CARDIAC ARRHYTHMIAS - E. V. Zatonskaya; G. V. Matyushin; N. G. Gogolashvili (Столичная издательская компания, 2017)
Arrhythmias are one of the most complex, insufficiently studied, and therefore one of the most urgent problems of modern cardiology. A wide spectrum of clinical manifestations of cardiac rhythm disorders (CRDs), their detection both in various diseases and in healthy people, necessitate the study of their prevalence in populations. In the majority of conducted epidemiological studies a single recording of electrocardiogram (ECG) was used. This is the most usable method for examination of large populations but a little informative for detecting arrhythmias. The small frequency of CRDs detected during ECG recording is due to the short duration of its registration. An increase in the duration of ECG recording (ECG recording for 2 minutes, continuous recording of 100 cardiocycles) leads to an increase in arrhythmias frequency. With a wide introduction in the practice of ECG monitoring by Holter as well as the use of individual recorders of electrocardiogram ("handheld ECG recording") data appeared indicating a much higher frequency of CRDs. Data obtained in numerous studies on the prevalence of arrhythmias are very contradictory and depend both on the characteristics of populations and on methodological approaches, which requires further epidemiological studies. At the same time, the main initiating point of such researches is the clinical significance of certain CRDs. However, if the clinical significance of ventricular tachyarrhythmias and atrial fibrillation does not currently cause any doubt, the clinical significance of extrasystoles is highly controversial, despite the high their prevalence, including this in prognostically unfavorable groups of patients. In recent years, the results of a number of studies have been published that allow to think about the adverse effects of both supraventricular and ventricular extrasystoles of the course of certain cardiovascular diseases. Very heterogeneous results of the performed studies, as well as data about the high clinical significance of individual CRDs, make further epidemiological studies in this field extremely urgent.